TEMBAK DITEMPAT DAN HAK ASASI MANUSIA - Masril Masril (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2015)
Shooting on sight and Human Right. The practice of shooting on sight was implementedin the past, Indonesia is a consitutional country (rechstaat) and not authoritarian country (machstaat).The Dead Penalty in Indonesia is mentioned in article 10 KUHP, and was implemented, but theprocess should be implemented in the sense of presumption of innocence, initiated by investigationand ended with binding decisions. Is the present practice of shooting on sight whether in accordancewith the law? In addition, do not violate the human right. The practice of law in constitutional countrysuch as Indonesia should be guaranteed